Pancasila Restoration as the National Philosophy (Law Research Review Quarterly, 2016)
Pancasila is not only a unifying and strengthening of the Indonesian nation, but also a living value in the midst of a pluralistic society. The long history of the Indonesian people provides an extraordinary and great experience, especially in terms of maintaining wholeness and harmony in diversity. Pancasila as the philosophy of life of the Indonesian people is not just five precepts, but rather the manifestation of real implementation and penetrates into every aspect of national and state life.